Qualitative Marketing Research to Improve Mountain Shelter Product Development for Romanian Mountain Tourism - Foris, Diana; Nicolau, Cristina; Foris, Tiberiu; Grecu, Vasile (International Journal of Economic Practices and Theories, 2015)
This paper aims at underlining the importance of mountain tourism within Romanian tourism, being centred on the research and development of mountain shelters so as to increase the tourists’ safety and convenience. In this respect, we shall analyse the Romanian market of mountain shelters, identifying the features of supply and demand of shelters both at public and private level and underlying the needs of developing a new product, hereinafter called eco modular shelter. As this new product has been previously designed and commissioned as a prototype by a professional team of engineers and professors, it will be the objective of this paper to identify how the eco modular shelter would meet its basic needs from the point of view of the authorities implied in the process of rescuing endangered lives. Therefore, there will be conducted a qualitative research with some members of the authorities who have been using these shelters both personally and professionally so as to determine if the eco modular shelter meets market needs and to identify its possible customers.